Catatan Perjuangan Bahasa Bali dalam Kurikulum 2013 - I Nyoman Suka Ardiyasa, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This article chronicles recent efforts to maintain Balinese language instruction in Balinese schools in response to the 2013 National Curriculum, which was to replace the former Competency-Based Curriculum (Kurikulum Berbasis Kompetensi). The new curriculum aimed to integrate local language instruction into the module for ‘local content/arts and culture’ (muatan lokal/seni budaya). It is important to note, however, that Balinese were not alone in reacting to the ‘disappearance’ of regional languages from the draft Curriculum for 2013. Rather, their desire to ensure the continuity of instruction in Balinese found parallels in other regions — such as Central Java and Sundanese-speaking parts of West Java — where similar struggles were afoot to uphold the teaching of local languages. It was feared that the younger generation would increasingly abandon regional languages should they no longer be taught in schools. Having laid out some of the consequences that would follow from abandoning the teaching of Balinese in schools, the article concludes with a series of suggestions toward the preservation of the Balinese language.
Keywords: Curriculum; Local content; Balinese language; Balinese culture; regional language